Development of visual basic based GUI for option a energy savings of IPMVP / Maxmillan David - David, Maxmillan (2014)
This paper presents the development of Graphical User Interface (GUI) for determining energy saving under Option A i.e. retrofit isolation from International Performance Measurement and Verification (IPMVP) protocol. The GUI is developed by using Microsoft Visual Basic 2010. In Option A of retrofit isolation, savings are determined by partial field measurement of the energy used to which an Energy Conservative Measure (ECM) was installed separate from the energy use of the rest of the facility. The GUI consists of three most applied Option A ECM projects, i.e. 1) lighting efficiency improvement, 2) lighting system retrofitting with dimmer and 3) chiller efficiency improvement. This Option A Visual basic-based GUI could guide and help Energy Service Company (ESCO) and facility owner to calculate energy saving that involves retrofit isolation energy efficiency projects adhere to IPMVP protocol.